Posterolateral plate fixation with Talarlock® is more stable than screw fixation in ankle arthrodesis in a biomechanical cadaver study. Issue 3 (June 2018) - Gutteck, N.; Martin, H.; Hanke, T.; Matthies, J.B.; Heilmann, A.; Kielstein, H.; Gradl, G.; Delank, K.S.; Wohlrab, D.
Highlights: A review of the literature failed to show up any further biomechanical analyses of the posterolateral plate arthrodesis In this study we present biomechanical analyses of the plate arthrodesis vs. screw arthrodesis in synthetic and cadaver ankle. Tests with synthetic bone specimens were used to establish the test program in preparation for tests with cadaver specimens. A promicing results could be showen. The authors expect advantages in treatment of patients with severe neuropatic deformity and poor bone quality. Abstract: Background: A number of studies report on limitations of the screw arthrodesis in severe malalignment of the hindfoot, neuropathic deformity, poor bone quality and osteoporosis. Methods: Fourteen anatomically correct polyurethane foam models of the right leg (Sawbones Europe, Malmö, Sweden) and eighteen fresh-frozen human lower leg specimens (9 pairs) were used for the comparative biomechanical testing. Results: The statistical analysis of the stiffness of the fixation developed a significant difference in favor of the plate in all test directions. Conclusions: The excellent biomechanical results are very promising and we hope for a reduction of the pseudarthrosis rate and shorten the postoperative treatment phase.